Evolving thermal conductivity upon formation and decomposition of hydrate in natural marine sediments. (15th October 2021) - Wei, Rupeng; Shi, Kangji; Guo, Xianwei; Wang, Tian; Lv, Xin; Li, Qingping; Zhang, Yi; Zhao, Jiafei; Yang, Lei
Highlights: The thermal conductivity of hydrate-bearing fine sediments is in-situ measured. A compaction of the sediments results in an increase of the thermal conductivity. Icing and reformation of hydrate could enhance the thermal conduction. Abstract: An insufficient heat supply has been recognized to majorly hinder the hydrate decomposition which is endothermic and thereby requires large amount of heat to sustain. Consequently, the thermal properties of the sediments play a vital role in the heat transfer process internally. Yet their evolution during hydrate formation and decomposition is complicated which couples phase transition, multiphase flow and component migration; relating knowledge still remain limited. Here, we report on a point-heat-source based measurement of local thermal conductivity of natural fine-grained sediments containing hydrates. The results show a significant effect of compaction on the effective thermal conductivity arising from the compressibility of the silty sediments. The evolution of components and their morphological behavior were found to majorly contribute to the variations of the thermal conductivity during hydrate formation, decomposition and reformation. A local icing and reformation of hydrate could also result in an enhancement of thermal conductivity benefiting from the better connected pore structure. Classic effective medium models were evaluated using our measured data; a hybrid fitting model by combining the self-consistent models was proposed, and the feasibility of the fitting model was verified using the data from the natural reservoir. The results of this study could provide insights into the effect of evolving hydrate phase on the resulting effective thermal conductivity of natural sediments; the findings would be helpful in a potential enhancement of the heat transfer process during gas production from hydrate reservoir to achieve an improved gas productivity.